Application of the Heart Metrics Method in Analyzing User Experience on the Rayz UMM Website - Wildan Suharso; Briansyah Setio Wiyono; Firman Firman (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2025)
The Rayz UMM Hotel website serves as the primary medium for conveying information about services and facilities, but so far, the quality of the user experience (UX) on the website has not been studied in depth. Based on the initial questionnaire results, there were also several negative responses that indicated dissatisfaction with the aspects of Happiness and Adoption. Therefore, a comprehensive UX evaluation is needed. This study uses the HEART Framework method, which covers five aspects, namely Happiness, Engagement, Adoption, Retention, and Task Success. The research instrument is a questionnaire with 20 questions distributed to website users, which is then analyzed through validity and reliability tests, hypothesis testing, and measurement of the level of usability. The results show that the variables of Happiness and Task Success are in the very high category, Retention is in the very high category, while Engagement and Adoption are in the very high category. These findings confirm that the Hotel Rayz UMM website has generally been able to provide a fairly good user experience, but still needs development in terms of navigation and system performance in order to optimize UX quality.